Pengembangan Lembar Kerja Peserta Didik (LKPD) Teks Eksplanasi pada Pembelajaran Bahasa Indonesia Kelas XI SMK - Dewi, Saskia Komala (Jurnal Guru Indonesia, 2023)
AbstractThe aim of this research is related to the problem formulation, namely, to produce a student worksheet (LKPD) with explanatory text that suits the needs of class XI students at the Cirebon City Tourism Vocational School. The method used in this development research uses a 4-D model, namely defining, planning, developing, and disseminating, but the dissemination stage was not carried out. This research was carried out from January to March 2023. The results of this research are the Student Worksheet (LKPD) for explanatory text consists of a cover, foreword, table of contents, introduction, competency mapping, explanatory text material, a summary of the material, assignments (individual, group, and evaluation), answer key, glossary, and bibliography. The material expert validator assessment 1 obtained a result of 86% and was included in the very feasible category. The assessment results from material expert validator 2 were in the decent category with a percentage of 75%, and material expert validator 3, namely the Indonesian language teacher, got a percentage score of 77% in the Decent category.  Tujuan penelitian ini berdasarkan rumusan masalah yakni, menghasilkan lembar kerja peserta didik (LKPD) teks eksplanasi yang sesuai dengan kebutuhan peserta didik kelas XI SMK Pariwisata Kota Cirebon. Metode yang digunakan pada penelitian pengembangan ini menggunakan model 4-D yakni pendefinisian (define), perencanaan (design), pengembangan (develop) serta penyebaran (disseminate), tetapi tahap disseminate tidak dilakukan. Penelitian ini dilaksanakan pada bulan Januari hingga Maret 2023. Hasil penelitian ini menyebutkan Lembar Kerja Peserta Didik (LKPD) teks eksplanasi terdiri dari sampul, prakata, daftar isi, pendahuluan, pemetaan kompetensi, materi teks eksplanasi, rangkuman materi, tugas (individu, kelompok dan evaluasi), kunci jawaban, glosarium, dan daftar pustaka. Penilaian validator ahli materi 1 mendapatkan hasil 86% dan termasuk kategori sangat layak. Hasil penilaian dari validator ahli materi 2 termasuk kategori Layak dengan persentase 75%,dan validator ahli materi 3 yaitu guru Bahasa Indonesia mendapatkan nilai persentase 77% dengan Kategori layak.